Co(OH)2 water oxidation cocatalyst-decorated CdS nanowires for enhanced photocatalytic CO2 reduction performance. Issue 29 (6th July 2021) - Xu, Yuyan; Xie, Zhongkai; Yu, Rui; Chen, Min; Jiang, Deli
Abstract : A Co(OH)2 nanoparticle decorated CdS nanowire (Co(OH)2 /CdS) based heterostructured photocatalyst was prepared. The optimal Co(OH)2 /CdS photocatalyst achieves a CO production rate of 8.11 μmol g −1 h −1 under visible light irradiation ( λ > 420 nm). Abstract : Photocatalytic CO2 reduction is a promising technology to resolve the greenhouse effect and energy crisis. In this work, a Co(OH)2 nanoparticle decorated CdS nanowire (Co(OH)2 /CdS) based heterostructured photocatalyst was prepared via a solvothermal and subsequent co-precipitation method, and it was used for photocatalytic CO2 reduction. The optimal Co(OH)2 /CdS photocatalyst achieves a CO production rate of 8.11 μmol g −1 h −1 under visible light irradiation ( λ > 420 nm), which is about 2 times higher than that of bare CdS. The experimental results show that a Co(OH)2 cocatalyst possesses a great capability of consuming holes, which promotes the oxygen-producing half-reaction and accelerates charge separation, thus enhancing the CO2 photoreduction performance of CdS. Notably, without using complex synthesis processes, hazardous substances or expensive ingredients, Co(OH)2 /CdS shows high light absorption, efficient charge separation and complete CO product selectivity. This work offers a new pathway for the construction of cost-effective photocatalytic materials to achieve highly efficient CO2 reduction activity by the integration of a Co(OH)2 cocatalyst.